The dynamics of strategic stability and instability. Issue 5 (19th October 2016) - Miles, Aaron R.
ABSTRACT: I apply a dynamic systems approach to define strategic stability and classify strategic systems as stable, unstable, or neutral, based on the nature of forces that strategic capabilities exert under perturbation away from equilibrium. Conceptualizing stability in this manner is helpful when considering its relationship to mutual vulnerability, its role in extended deterrence relationships, and prospects for maintaining stability along proposed paths to disarmament. Traditional U.S. policy objectives do not appear to distinguish between true stability and neutral stability, and traditional definitions of strategic stability describe neutral stability. True strategic stability is an unlikely policy objective for the United States.